1982
DOI: 10.4039/ent1141083-11
|View full text |Cite
|
Sign up to set email alerts
|

Populations of Beneficial and Pest Arthropods in an Organic and a Pesticide Treated Apple Orchard in British Columbia

Abstract: A 2-year study was conducted in an organic, essentially pesticide-free orchard and in one which followed a complete pesticide program to assess populations of beneficial arthropods. There were far more beneficial species in the pesticide-free orchard both on the trees and in the cover crop. Spiders increased dramatically in the organic orchard and relatively few spiders were found in the sprayed orchard. Pest species were below treatment thresholds in both orchards with the exception of codling moths. By the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
3
0
2
Order By: Relevance
“…These very traits may in fact be characteristic of taxonomic groups that are most diverse and most abundant in orchards, such as the Coccinellidae (Snyder 2009) and Araneae (Bogya and Mols 1996). Our results are in agreement with earlier surveys conducted in apple orchards of North America, which also have documented high diversity of spiders (Dondale 1956;McCaffrey and Horsburgh 1980;Brown et al 2003), true bugs (Oatman et al 1964;Madsen and Madsen 1982), lacewings (Szentkirályi 2001;Horton et al 2002), and ladybeetles (Brown and Schmitt 2001). The taxonomically most diverse groups in this study were the Coccinellidae, with 22 identified species, and the Araneae, which included representatives from 14 families.…”
Section: Orchard Assemblagessupporting
confidence: 92%
See 2 more Smart Citations
“…These very traits may in fact be characteristic of taxonomic groups that are most diverse and most abundant in orchards, such as the Coccinellidae (Snyder 2009) and Araneae (Bogya and Mols 1996). Our results are in agreement with earlier surveys conducted in apple orchards of North America, which also have documented high diversity of spiders (Dondale 1956;McCaffrey and Horsburgh 1980;Brown et al 2003), true bugs (Oatman et al 1964;Madsen and Madsen 1982), lacewings (Szentkirályi 2001;Horton et al 2002), and ladybeetles (Brown and Schmitt 2001). The taxonomically most diverse groups in this study were the Coccinellidae, with 22 identified species, and the Araneae, which included representatives from 14 families.…”
Section: Orchard Assemblagessupporting
confidence: 92%
“…The diet of the spider community in orchard ecosystems is relatively poorly studied, but is likely to include pests from a range of taxonomic groups (Bogya and Mols 1996). Collections of predatory true bugs included primarily Miridae, as noted also in other geographic regions (Madsen and Madsen 1982; Brown and Schmitt 2001). Deraeocoris brevis , which was very abundant in collections, is known to be an important predator of soft-bodied Homoptera such as aphids and psyllids (McMullen and Jong 1967; Unruh et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hedgerows, however, are subject to edge effects that can increase the risk of brood parasitism by Brown‐headed Cowbirds or of predation ( Rodenhouse & Best 1983). Another potential advantage of organic farms may be abrogation of chemical use, which leads to healthier invertebrate faunas ( Madsen & Madsen 1982; Drinkwater et al 1995; Freemark & Boutin 1995). Some of the latter benefits may be lost because of soil erosion or because wind causes some agrochemical drift from adjoining farms (e.g., Marrs et al 1989.…”
Section: Discussionmentioning
confidence: 99%
“…These control plots were designed to receive ambient pest levels without intervention, and so differ from commercial ORG farms in several important ways, including the appli-ll09 cation of synthetic fertilizers and herbicides, the absence of alternative insect pest controls, and the spatial and temporal scale 0f the experiment. These discrepancies may explain why on-farm comparisons of crop damage and pest population levels do not, in general, support the notion that ORG management practices exacerbate pest outbreaks (e.g., Madson and Madson 1982, Sengonca and Bruggen 1989, Hesler et al 1993.…”
Section: Yield Herbivory and Arthropod Communitiesmentioning
confidence: 98%